2016
DOI: 10.1063/1.4964620
|View full text |Cite
|
Sign up to set email alerts
|

Rheology behaviors of stable electrohydrodynamic direct-write jet

Abstract: Electrohydrodynamic direct-write (EDW) is a novel direct-write technology to fabricate micro/nano-structures from viscoelastic solution, which had displayed great application potential in organic electronic device. Due to the shorter spinneret to substrate distance, the rheology behaviors of EDW charged jet played an important role in defining the line width or diameter of the direct-written micro/nano-structures. High speed camera is utilized to observe the rheology process of EDW charged jet, and solidified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This imaging device should be able to observe comprehensive details in a cost-effective way so as to observe the jet triggering voltage and the lowest voltage for stable EHDP process. Researchers have studied Taylor cone modes with different viscous solutions[ 8 ]. When high viscous solutions are fed into the EHDP system, the jet ejection velocity can be comparable with that of the computer-controlled precision stage in the range of 50–400 mm/s[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This imaging device should be able to observe comprehensive details in a cost-effective way so as to observe the jet triggering voltage and the lowest voltage for stable EHDP process. Researchers have studied Taylor cone modes with different viscous solutions[ 8 ]. When high viscous solutions are fed into the EHDP system, the jet ejection velocity can be comparable with that of the computer-controlled precision stage in the range of 50–400 mm/s[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, when viscosity is changed ( ), as increases, the operating range of dimensionless flow rate ( ) increases for , and the operating range of dimensionless voltage ( ) increases for . Although the results showed that increasing viscoelasticity of the ink is beneficial to the formation of a stable cone jet, whereas an excessively high viscoelasticity would increase the jet diameter thus decreasing the resolution of patterns 105 .…”
Section: For Electrohydrodynamic Jet Printingmentioning
confidence: 88%
“…24,25 The charge repulsion force F q enhances the instable motion of the charged jet and decreases the diameter of the nanofiber. 26,27 …”
Section: -6mentioning
confidence: 99%